CFD Analysis on Liquid Overflow of Ionic Compressors Considering Valve Resistance - Xiang Kang; Zekun Liu; Yuan Lv; Yun Li (Chemical Engineering Transactions)
Ionic compressors are promising applied in hydrogen refueling stations. Ionic liquid is adopted inside cylinders for sealing and cooling. Liquid slugging may occur but was rarely referred to in the previous studies, since former modeling ignored the effects of valve resistance. This paper proposes a method to involve valve resistance into gas-liquid simulation of ionic compressors. Valve flow coefficient is derived from the relationship of pressure-drop and flow rate through the valve. A multicycle simulation is conducted based on the Volume of Fluid (VOF) method. Liquid slugging and sudden pressure rise can be observed from the proposed method. Results show that liquid overflow per cycle can be separated into two parts: liquid slugging part and entrained part. Liquid slugging abates and finally disappears as the initial liquid fraction per cycle decreases. Pressure caused by liquid slugging increases beyond 1.5 times discharge pressure, demonstrating that liquid slugging may lead to deformation or even fraction of pressure-bearing parts. The results can validate the significance of involving valve resistance into the simulation model. A method is proposed to judge whether liquid slugging will occur. Predicted liquid slugging time has a good agreement with the CFD results. This study can provide a reference for numerical calculation of liquid overflow and slugging of ionic compressors.